Restoring public trust in COVID-19 vaccine among Africans, Caribbean, and Black Canadians using Community based participatory research (CBPR) - Josephine Etowa; Amoy Jacques; Luc Malemo; Bishwajit Ghose; Egbe B. Etowa; Charles Dabone; Sylvia Sangwa (Discover Public Health)
Abstract Background The COVID-19 pandemic had a significant global impact predominantly among Africans, Caribbean and Black (ACB) Canadians. ACB people experienced higher infection and recovery rates, greater health risks, and access to care. Evidence shows that public mistrust, due to anti-Black racism and historical trauma contributed to low vaccine uptake among ACB populations. Our study examined multi-level and intersectional issues impacting vaccine uptake and acceptance in Ottawa. This paper will focus on the theme of agency. Methods A mixed methods research (MMR) approach guided this study using the socio-ecological model (SEM), intersectionality lens, and community-based participatory research principles to generate qualitative results. The sample included 49 ACB participants involved in community focus group discussions (FGDs) and 27 participants from our World Cafe. The sample population from the FGDs included service providers (20), social workers (15), doctors (3), and nurses (3) and others (8) who were predominantly Black African (70%), mostly female (80%), age range was 35–44 (33%) with high school diplomas (40%). The sample for the World Cafe included ACB members from community organizations, public health services, and peer-equity navigators (PENs). Data were recorded digitally, transcribed verbatim, analyzed inductively. Data analysis methods were thematic analysis including inductive coding using NVivo software and rigor methods were member-checking and external audits. Results Our data showed rebuilding public trust is possible by bridging knowledge gaps on vaccine information, increasing service providers’ cultural competence capacity, and providing governance/leadership opportunities for ACB communities. Conclusion Restoring public trust will require dismantling racism by prioritizing ACB community’ needs, proactive and accessible culturally appropriate messages, and opportunities to develop policies to improve health outcomes.